ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT INFLASI DI INDONESIA - Nadiah Nadiah; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research aims to examine the effect of sharia monetary policy transmissionagainst inflation rate in Indonesia partially and simultaneously. The approach that is used in this research is the quantitative approach, using multiple linear regression analysis technique and quantitative descriptive. The data that is used is secondary data from the official website of Bank Indonesia and the Financial Services Authority. The result of this research indicates that PUASand partial sharia financing have partial positive significant effect on inflation rate in Indonesia, while JUB (M1) has a partially negative significant effect on inflation rate in Indonesia. Simultaneously PUAS, sharia financing and JUB (M1) have positive significant effects against inflation rate in Indonesia at the level of 48,7%, while the remaining 51,3% is influenced by other variables that aren’t examined by the writer.   REFERENCESBofinger, Peter. 2001. Monetary Policy: Goals, Institutions, Strategies, and Instruments. Oxford University Press.De Bondt, G.J. 2000. Financial Structure and Monetary Transmission in Europe. Edward Elgar Publisher.Ghozali, Imam. 2011. Aplikasi Analisis Multivariate dengan Program IBM SPSS 19. Semarang: Universitas Diponegoro.Kakes, Janes. 2000. Monetary Transmission in Europe: The Role of Financial Markets and Credit. Edward Elgar: Cheltenham.Mankiw, N. Gregory. 2006. Principles of Economics. Pengantar Ekonomi Makro. Edisi Ketiga, Salemba Empat Jakarta.Mishkin, Frederic S. 1996. “The Channel of Monetary Transmission: Lesson for Monetary Policy”, NBER Working Paper.Nanga, Muana. 2005. Makro Ekonomi Teori, Masalah, dan Kebijakan. Jakarta: PT. Raja Grafindo.Pohan, Aulia. 2008. Kerangka Kebijakan Moneter dan Implementasinya di Indonesia. Jakarta: PT. RajaGrafindo Persada.--------. 2008. Potret Kebijakan Moneter Indonesia. Jakarta: PT. RajaGrafindo Persada.Rusydiana, Aam Slamet. 2009. “Mekanisme Transmisi Syariah pada Sistem Moneter Ganda di Indonesia”. Buletin Ekonomi Moneter dan Perbankan, Vol. 11 No. 4, Edisi April.Setiarso, Oke. 2011. “Pengaruh Instrumen Moneter (Open Market Operation, Pasar Uang Antar Bank dan Reserve Requirement) Dalam Dual Monetary System Terhadap Volume Uang Primer Dalam Masa Krisis di Indonesia”. JEBA, Vol. 13, No. 1, Maret 2011.Warjiyo, P dan Solikin. 2003. Kebijakan Moneter di Indonesia. Buku Seri Kebanksentralan No. 6. Pusat Pendidikan dan Studi Kebanksentralan, Bank Indonesia, Jakarta.--------. 2004. Mekanisme Transmisi Kebijakan Moneter di Indonesia. Buku Seri Kebanksentralan No. 11. Pusat Pendidikan dan Studi Kebanksentralan, Bank Indonesia, Jakarta.www.bi.go.id.www.ojk.go.id.